Children, adolescents, and young adults hospitalized with COVID‐19 and diabetes in summer 2021. Issue 7 (5th August 2022) - Agathis, Nickolas T.; Womack, Lindsay S.; Webber, Bryant J.; Choudhary, Rewa; Wanga, Valentine; Ko, Jean Y.; Dupont, Hannah; Imperatore, Giuseppina; Koumans, Emilia H.; Saydah, Sharon; Kimball, Anne A.; Siegel, David A.; et al.
Abstract: Introduction: More information is needed to understand the clinical epidemiology of children and young adults hospitalized with diabetes and COVID‐19. We describe the demographic and clinical characteristics of patients <21 years old hospitalized with COVID‐19 and either Type 1 or Type 2 Diabetes Mellitus (T1DM or T2DM) during peak incidence of SARS‐CoV‐2 infection with the B.1.617.2 (Delta) variant. Methods: This is a descriptive sub‐analysis of a retrospective chart review of patients aged <21 years hospitalized with COVID‐19 in six US children's hospitals during July–August 2021. Patients with COVID‐19 and either newly diagnosed or known T1DM or T2DM were described using originally collected data and diabetes‐related data specifically collected on these patients. Results: Of the 58 patients hospitalized with COVID‐19 and diabetes, 34 had T1DM and 24 had T2DM. Of those with T1DM and T2DM, 26% (9/34) and 33% (8/24), respectively, were newly diagnosed. Among those >12 years old and eligible for COVID‐19 vaccination, 93% were unvaccinated (42/45). Among patients with T1DM, 88% had diabetic ketoacidosis (DKA) and 6% had COVID‐19 pneumonia; of those with T2DM, 46% had DKA and 58% had COVID‐19 pneumonia. Of those with T1DM or T2DM, 59% and 46%, respectively, required ICU admission. Conclusion: Our findings highlight the importance of considering diabetes in the evaluation of children and young adults presenting with COVID‐19; the challenges of managing young patients who present with both COVID‐19 and diabetes, particularly T2DM; and the importance of preventive actions like COVID‐19 vaccination to prevent severe illness among those eligible with both COVID‐19 and diabetes.